Government subsidy research on the application of IoT technology in contract-farming supply chain - Xideng Zhou; Yuan Peng; Bing Xu; Wan-zhi Xiong; Xiao-mei Peng (PLoS ONE, 2025)
Existing research have not yet focused on the mechanism of Internet of Things(IoT) technology’s impact on the contract-farming supply chain.We introduce the IoT technology into the contract-farming supply chain with financing, successively construct decision models for the contract-farming supply chain under the scenarios of no subsidy policy, interest rate subsidy policy, and cost subsidy policy. The results show that an increase in bank interest rate will reduce the level of IoT application, purchasing price, members benefits. When the financing interest rate is within a certain range, members benefits in the case of interest rate subsidy policy are greater than the corresponding values in the case of cost subsidy policy. In the case of no subsidy policy, interest rate subsidy policy, and cost subsidy policy, the application level of the IoT, purchasing price, and the company benefit are positively correlated with the output effect factor of the IoT technology. The farmer will actively invest in the IoT only when the cost-reducing effect of IoT is substantial. When the government’s subsidy expenditure is equal, if the goal is to increase social welfare, the government should adopt the interest rate subsidy policy; if the goal is to promote the popularization of IoT and help impoverished farmers, the government should adopt the cost subsidy policy.